FLUID-LABVIR, an immersive online platform as complement to enhance the student’s learning experience in experimental laboratories of Fluid Mechanics and Fluid Engineering - del Álamo, Ana Cruz; Megía, Pedro; Plaza, Jorge; Casado, Cintia; Van Grieken, Rafael; Martínez, Fernando; Molina, Raúl (Education for chemical engineers, 2022)
Practice in experimental laboratories is a fundamental activity in the Degrees in Science and Engineering. FLUID-LABVIR platform is an attempt to innovate in the experience of students who must carry out laboratory practices, particularly in engineering and fluid mechanics subjects, by providing them with a tool (guide prepared as a website) adapted to the context of current media in a multi-platform web format (PC, mobile, tablet). This guide not only includes the theoretical foundations and the measurements which must be taken during the practice, but also includes images, animations, and explanatory videos of the handling of the practice made by teachers to support the theoretical content. It is also an additional tool to practice the handling of the experimental installation through an immersive simulator that reproduces the operation of the practice as faithfully as possible, including calibration errors of measuring equipment during the practice, saturation of indicator elements, etc. On this website, students have the possibility of downloading or accessing the practice simulator via the MyApps platform, so that they can work virtually with the demonstrative equipment, following the steps and taking the measurements that they would take in person in the laboratory. This simulator is accompanied by a short video tutorial showing how to use the simulator and how it would be operated to reproduce the handling and taking of measurements in the experimental practice. The virtual laboratory activity was implemented during the 2020/21 academic year, through three practices/simulators: Head Loss in Pipes (FM-HLP), Flow in Open Channel (FM-OC), and Wind Tunnel (FM-WT). The students considered the activity as a good complement to the practical learning before using it in the laboratory, indicating that the script seemed more attractive to them than the previous methodology based on written manuals of each practice in the laboratory. The theory and practice are also presented in more depth on the website. The students highlighted that, although it is always preferable to carry out the experimental practice in person, the immersive simulator seemed to them to be a good substitute, and the website was accessible and easy to use. The simulator reproduced the handling (stages, devices, etc.) of the experimental installation in a very acceptable way, and in some cases, they used the simulator to obtain additional data to prepare the final report of the practices. As a result of this work and this experience, the virtual laboratory activity will be offered as a complement to the traditional syllabus in the labs for subsequent academic years. •FLUID-LABVIR, an online platform as innovative way to teach experimental laboratories.•Webpage is based on audio-visual material and an immersive simulator of installation.•FLUID-LABVIR is open to all the students and educator community.•The students consider FLUID-LABVIR a good complement to the practical learning.